Crowdsourcing an emotional wardrobe - Hughes, L.; Atkinson, Doug; Berthouze, N.; Baurley, S. (2012)
Selecting clothing online requires decision-making about sensorial experiences, but online environments provide only limited sensorial information. Inferences are therefore made on the basis of product pictures and their textual description. This is often unreliable as it is either based on the designer's understanding of the product or deprived of perceptual content due to the difficulty of expressing such experiences. Using a purpose built website that combines and cross references multi-modal descriptive media, this study aims at investigating the possibility of using crowdsourcing mechanisms and multi-modal language to engage consumers in providing enriched descriptions of their tactile experiences of garments.